Elevate the debate : a multi-layered approach to communicating your research - Schwabish, Jonathan A. (John Wiley & Sons, Inc., 2020)
"Many researchers and scholars resist the idea of developing a communication strategy, either thinking that someone else will do it, their work will be naturally discovered, or that it doesn't matter. Developing a communication strategy--and implementing that strategy--recognizes the importance of making research accessible to a wider audience, decision makers, and policymakers--even the public. Elevate the Debate will help researchers of all types more effectively communicate their work. Elevate the Debate is written in a practical voice and provides a starting roadmap for researchers and organizations interested in helping their research have a greater impact. In this book, readers will learn practical strategies and skills that will enable them to communicate their work to their desired audiences"--